350 Factors associated with acute kidney injury in patients undergoing open gynecologic surgery on an enhanced recovery after surgery pathway. (13th November 2020) - Huepenbecker, S; Iniesta, M; Ramirez, P; Pitcher, B; Vaughn, M; Mena, G; Lasala, J; Meyer, L
Abstract : Introduction: Enhanced recovery after surgery (ERAS) pathways use goal-directed fluid therapy (GDT) to reduce postoperative complications from fluid imbalance. Our study aimed to determine the incidence and risks of acute kidney injury (AKI) in patients on an ERAS pathway. Methods: AKI was defined as acute risk, injury, or failure by RIFLE criteria. Chi-squared, Fisher's Exact, and Wilcoxon rank-sum tests were used. Propensity score analysis with 1:1 matching compared AKI in ERAS and pre-ERAS cohorts and modeled the probability of AKI as a function of ERAS. Results: Among 1127 patients on an ERAS pathway, 140 had AKI (12.4%, 95% CI 10.5%-14.5%). Patients with AKI were more likely to be older (median age 65 vs 57, p<0.001) and black (18% vs 11%, p=0.04) with more comorbidities (Charlson Comorbidity Index ≥3 in 74% vs 48%, p<0.001) including diabetes (21% vs 12%, p=0.005), and had higher estimated blood loss (median 400 vs 250 mL, p<0.001), post-operative hypotension (6% vs 2%, p=0.01), readmission (20% vs 9%, p<0.001), and reoperation (5% vs 1.3%, p=0.008) with longer median hospital stay (4 vs 3 days, p<0.001). In 140 matched pairs, 9 pre-ERAS patients (6.4%) and 17 ERAS patients (12.1%) had AKI, with no effect of ERAS on AKI incidence (OR 0.5, p=0.11). Conclusions: A total of 12.4% of patients developed AKI, but ERAS itself was not associated with AKI incidence in the matched cohort. Highest AKI risk factors included older age, black race, more comorbidities, and blood loss.